STRATEGI MARKETING PUBLIC RELATIONS DESA MANGROVESARI BREBES SEBAGAI DESA WISATA BERBASIS MANGROVE - Destiara, Felinka; Fauzi, Rizky (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2023)
This research wants to see how the marketing public relations strategy of Mangrovesari village as a mangrove-based tourism village. This research method was carried out using a descriptive qualitative approach. Informants in this study were from internal Mangrovesari villages, business partners, and tourists from Mangrovesari villages. The concept used in this study from Thomas L Harris consists of a Push strategy, a Pull strategy and a Pass strategy. Data collection was carried out by in-depth interviews and documentation from the internet as additional data or information. The data analysis techniques use coding techniques and data validity techniques use triangulation. The conclusion in this study is that the marketing public relations strategy carried out by Mangrovesari village with the concept of Push strategy, Pull strategy, and Pass strategy concepts are interrelated with each other and can help Mangrovesari village to manage, develop, promote and form positive public opinion as a village. mangrove-based tourism, thus making tourists more familiar with and interested in coming to Mangrovesari village.